Association between polymorphisms in the gene encoding the vitamin D receptor, lipid profile and anthropometric parameters in elderly Brazilians - Nunes, Ivone Freires de Oliveira Costa; de Carvalho, Cecilia Maria Resende Gonçalves; Silva, Gabriella Magalhães; dos Santos, Gleyson Moura; da Silva, Maria Eduarda Raielly; Silva, Elane Natielly da Conceição; de Araújo, Nauale Lopes; dos Santos, Lynda Sthefanny Alves; Sousa, Laura Beatriz Guimarães; Lodoro, Gleicer Vívian da Silva; Gomes, Ruth Hellen do Nascimento; Val, Sarah Celeste Rodrigues de Sousa (Seven Editora, 2024)
Polymorphisms in the vitamin D receptor gene are associated with the severities of several diseases, including overweight and cardiovascular disease. In addition, vitamin D is an important determinant of health and has several functions in bone homeostasis and in various physiological and metabolic mechanisms. From this perspective, this study aimed to evaluate whether there is an association between the genetic variants Fok1 (rs2228570) and Bsm1 (rs1544410) with circulating metabolic markers of the lipid profile and anthropometric measurements in the elderly. This is a cross-sectional study conducted with 173 elderly people from Teresina, Piauí State, Brazil, whose sociodemographic and health characterization occurred through interviews. 25-hydroxyvitamin D [25(OH)D] was measured by chemiluminescence. The cut-off values used as a reference for serum lipids were from the Update of the Brazilian Guideline on Dyslipidemias and Prevention of Atherosclerosis. Genotyping was performed using the restriction fragment length polymorphism technique. The results showed that there were no statistically significant differences between the association of VDR FokI and BsmI gene polymorphisms with BMI, blood pressure and vitamin D concentrations. However, elderly carriers of the BsmI genotype, specifically Bb heterozygotes, were associated with lower values of triglycerides and HDL-cholesterol. DOI:https://doi.org/10.56238/sevened2024.016-010